"Multipoint Force Feedback" Leveling of Massively Parallel Tip Arrays in Scanning Probe Lithography. Issue 35 (16th June 2015) - Noh, Hanaul; Jung, Goo‐Eun; Kim, Sukhyun; Yun, Seong‐Hun; Jo, Ahjin; Kahng, Se‐Jong; Cho, Nam‐Joon; Cho, Sang‐Joon
<x xml:space="preserve">Abstract</x> Nanoscale patterning with massively parallel 2D array tips is of significant interest in scanning probe lithography. A challenging task for tip‐based large area nanolithography is maintaining parallel tip arrays at the same contact point with a sample substrate in order to pattern a uniform array. Here, polymer pen lithography is demonstrated with a novel leveling method to account for the magnitude and direction of the total applied force of tip arrays by a multipoint force sensing structure integrated into the tip holder. This high‐precision approach results in a 0.001° slope of feature edge length variation over 1 cm wide tip arrays. The position sensitive leveling operates in a fully automated manner and is applicable to recently developed scanning probe lithography techniques of various kinds which can enable "desktop nanofabrication."